2017
DOI: 10.1111/jog.13308
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine for pain control during intrauterine device insertion

Abstract: Lidocaine spray is a good option for reducing the pain experienced during insertion of an IUD. It reduces pain related to both tenaculum use and IUD insertion. Spray application is both easy and rapid. Paracervical lidocaine injection also reduces pain during IUD insertion, but has no effect on tenaculum-related pain; moreover, the injection itself is painful. Therefore, this option is not a plausible method for reducing pain during IUD insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…However, there was an increase in pain associated with the lidocaine injection (30 vs 8 mm, P = 0.003) . The study by Karasu et al described above found that 10 mL 2% lidocaine injection, a dose higher than that used in most clinics, led to a lower mean pain score at placement when compared with LP cream and control (no anesthesia) (2.9 ± 1.4 vs 4.0 ± 1.7 vs 4.25 ± 1.9) but no difference in the proportion of women experiencing no pain at placement (2.1% vs 1.9% vs 2.0%). Two RCTs comparing lidocaine paracervical block with nonsteroidal anti‐inflammatory drugs (NSAIDs) and placebo (400 mg ibuprofen and 500 mg oral naproxen/placebo, respectively) found no differences in mean pain scores during placement …”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…However, there was an increase in pain associated with the lidocaine injection (30 vs 8 mm, P = 0.003) . The study by Karasu et al described above found that 10 mL 2% lidocaine injection, a dose higher than that used in most clinics, led to a lower mean pain score at placement when compared with LP cream and control (no anesthesia) (2.9 ± 1.4 vs 4.0 ± 1.7 vs 4.25 ± 1.9) but no difference in the proportion of women experiencing no pain at placement (2.1% vs 1.9% vs 2.0%). Two RCTs comparing lidocaine paracervical block with nonsteroidal anti‐inflammatory drugs (NSAIDs) and placebo (400 mg ibuprofen and 500 mg oral naproxen/placebo, respectively) found no differences in mean pain scores during placement …”
Section: Resultsmentioning
confidence: 91%
“…Two RCTs reported lower placement‐related pain scores with lidocaine spray (net 40 mg) when compared with 2 g lidocaine cream or 10 mL lidocaine (20 mg/mL) injection and placebo . In the study by Karasu et al, a greater number of women in the lidocaine spray group reported no pain with placement compared with the injection and cream group (25.5% vs 1.9% vs 2.1%; P < 0.001). In the study by Aksoy et al, use of lidocaine spray reduced mean pain scores by 2.2 cm when compared with placebo (1.01 ± 1.20 vs 3.23 ± 1.60, P > 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations